Load Balancing in IoT Applications Using Consistent Hashing - Shvayka, A.I. (Электронное моделирование, 2016)
The paper gives a systematic analysis of the load balancing methods within the scope of the most common cases of the Internet of Things use and network protocols. It also presents the architecture of a load balancing system that supports HTTP, MQTT and CoAP protocols and utilizes a consistent hashing algorithm.